The Determination of Shock Accelerations on a Small Nuclear Power Plant Structural Elements When Falling to the Surface - O. A. Gubeladze; A. R. Gubeladze (Глобальная ядерная безопасность)
The article conducts research one of the expansion phase of emergency with an Intercontinental Ballistic Missile, accompanied by an carrier explosion, an ejection of the reentry vehicle from a silo and its subsequent fall. The simulation of the collision of the reentry vehicle with a weakly deformable barrier in the event of fall is performed, the result calculation valuation and experiment are carried out.